Grouping Education Students at Pusdikjas Institutions of The TNI-AD's Disjasad Using the K-Means Clustering Method - Pramudjianto, Imam Wibowo; Ningsih, Ade Kania; Komarudin, Agus (Enrichment: Journal of Multidisciplinary Research and Development, 2023)
The Military Physical Education Center, known by the abbreviation Pusdikjasmil, is an implementation body that is directly under the TNI AD. Pusdikjas has the task of providing education in the military physical field to support the duties of the Indonesian Army. At the Pusdikjas agency, student data is obtained from the addition of students attending education each year. The process of admitting students to Pusdikjas institutions produces abundant value data and is repeated every year. By using data mining techniques, abundant student data can be grouped and analyzed to find information that is useful for Pusdikjas agencies. The algorithm used in this research is K-means clustering. The data used from 2018 - 2022 was 1428 data on coaching education students, with the variables used being NRP, attitude & and behavior, knowledge & and skills, and physical. Processed using the JavaScript programming language, this research produces optimal clusters, namely 2 clusters. cluster 1 with a total data of 751 students in cluster 1 describes a very satisfactory category of students, and cluster 2 with total data of 676 students. Cluster 2 describes the satisfactory student category. As for testing the quality of the clusters contained in the system using silhouette with results reaching 0.6543347543126016.